2019
DOI: 10.1039/c9md00054b
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the genome mining ofAspergillussecondary metabolites (covering 2012–2018)

Abstract: This review covers advances made in genome mining SMs produced by Aspergillus nidulans, Aspergillus fumigatus, Aspergillus niger, and Aspergillus terreus in the past six years (2012–2018). Genetic identification and molecular characterization of SM biosynthetic gene clusters, along with proposed biosynthetic pathways, is discussed in depth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 165 publications
(103 reference statements)
1
54
0
Order By: Relevance
“…These SMs play diverse ecological roles in fungal defense, communication, and virulence [13], and some of them, owing to their toxic activity, are collectively known as mycotoxins. In recent years, there have been many reviews on the production of theses type of compounds by species from the genus Aspergillus [12,[14][15][16][17][18][19][20], and specifically, A. fumigatus has the potential to produce 226 of these compounds [21]. The genes responsible for the synthesis of SMs are commonly associated with biosynthetic gene clusters [16,22,23] and the A. fumigatus genome contains between 26 and 36 putative SMs gene clusters depending on the authors [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…These SMs play diverse ecological roles in fungal defense, communication, and virulence [13], and some of them, owing to their toxic activity, are collectively known as mycotoxins. In recent years, there have been many reviews on the production of theses type of compounds by species from the genus Aspergillus [12,[14][15][16][17][18][19][20], and specifically, A. fumigatus has the potential to produce 226 of these compounds [21]. The genes responsible for the synthesis of SMs are commonly associated with biosynthetic gene clusters [16,22,23] and the A. fumigatus genome contains between 26 and 36 putative SMs gene clusters depending on the authors [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…LC-MS analysis revealed that the pheromone module proteins are required for the regulation of SM production (Figure 4). A. fumigatus is a prolific producer of SMs, most notably the immunosuppressive agent gliotoxin (Hof and Kupfahl, 2009;Romsdahl and Wang, 2019). It was evident that the deletion of any of the five pheromone module genes results in dramatic reductions in gliotoxin production in comparison to a wild type strain ( Figure 4A).…”
Section: Discussionmentioning
confidence: 99%
“…A. fumigatus growth and virulence is greatly influenced by the ability of this species to produce various bioactive compounds known as secondary metabolites (SMs), which can possess a myriad of properties. A. fumigatus has 40 predicted SM core synthase enzyme-encoding genes, 19 of which have been shown to produce downstream products (Romsdahl and Wang, 2019). The production of gliotoxin, a SM with immunosuppressive properties is a major contributor to virulence (Hof and Kupfahl, 2009) and is implicated in 96% of cases of A. fumigatus infections (Ghazaei, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The uncharacterised NRPS encoding An13g03040 as well as seven genes of this cluster expressed specifically in the 2 days IL and 2 d KMS conditions. Expression of the uncharacterised cluster An12g07060-An12g07110 [74] increased to considerable levels on late cultivation time points (Fig. 6f ).…”
Section: Novel and Known Secondary Metabolite Gene Clusters Induced Amentioning
confidence: 96%